Successful Cryopreservation of Spermatogonia Stem Cells of Neotropical Catfish (Rhamdia quelen) and Enriched Germ Cell Transplantation into Common Carp (Cyprinus carpio) Testes - Rosa, Ivana F. [UNESP] (2023)
Cryopreservation and transplantation of spermatogonial stem cells (SSCs) offer new possibilities in the conservation of valuable genetic resources. Therefore, the present study developed a cryopreservation method for whole testicular tissue and for spermatogonial stem cells of jundia catfish (Rhamdia quelen) and developed an enriched germ cell transplantation of jundia catfish into depleted common carp (Cyprinus carpio) testes. Our findings from whole testes indicate that the cryoprotectants MeOH (1.3 M), DMSO (1.4 M), and EG (1.4 M) resulted in high cell viability rates of 67%, 62%, and 51.5%, respectively. Notably, in the case of enriched post-thaw SSCs, DMSO exhibited the highest cell viability at 27%, followed by EG at 16% and MeOH at 7%. Additionally, we observed the successful colonization and proliferation of jundia germ cells within the recipient gonads of common carp following transplantation. Notably, Sertoli cells were identified in the recipient gonads, providing support to the stained donor germ cells and indicated the formation of cysts. Our data suggest that cryopreserving entire testicular tissue presents a viable alternative to cryopreserving isolated testicular cells, and the spermatogonial cells isolated from testes of jundia retained transplantability characteristics. Nonetheless, more investigations are required to reach the goal of functional gamete and to assess the effectiveness of transplantation using these cryopreserved tissues. Taken together, proper cryopreservation methodology and transplantation technology could aid the preservation practice of fish genetic resources.